Education Analysis and Entrepreneurship Training For Micro, Small and Medium Enterprises (SMEs) in Sentra Tenun Ikat Lamongan Regency - Sulistyo Sulistyo; Sholikhan Sholikhan; Sri Rahayuningsih (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this study is to describe management education and entrepreneurship training for craftsmen tenun ikat in Lamongan regency. The type of research used is descriptive qualitative which data collection using interview and documentation techniques. Data analysis consists of data reduction, data presentation, and conclusion. The results showed that education and training management began with the planning and determination of training participants, analysis of training needs of the participants, the determination of the goals and objectives of the training and the determination of program content. Implementation of entrepreneurship training plays a role in forming motivation and entrepreneurial intentions for craftsmen tenun ikat in Lamongan regency. It is necessary to evaluate the implementation of the training which is implemented within 4-5 months after the implementation of the training, with the aim to know the development of business owned by participants who have followed the training.